2005
DOI: 10.1097/01.mph.0000181430.71176.b7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Oral Etoposide for Childhood Recurrent Ependymomas

Abstract: In this study the authors retrospectively evaluated the feasibility and effectiveness of prolonged oral etoposide therapy in children with recurrent ependymoma. Twelve ependymoma patients with documented recurrent or persistent disease were treated between May 1998 and October 2003. All patients were treated monthly with oral VP-16 administered at a dose of 50 mg/m2/d for 21 days, with a 7-day interval between cycles, for a planned minimum number of six cycles. Response (complete plus partial) after two cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…In the only osteosarcoma study on Oral Etoposide 50 mg/m 2 /daily for 14 days as monotherapy, Kebudi et al [7] reported a 15% response rate (RR) in relapsed pediatric patients. Sandri et al [8] reported a successful use of Oral Etoposide at 50 mg/m 2 in children with recurrent ependymomas, showing a 40% RR. Oral Etoposide is well tolerated, with only mild adverse drug reactions like nausea, leucopenia, and alopecia.…”
Section: Introductionmentioning
confidence: 99%
“…In the only osteosarcoma study on Oral Etoposide 50 mg/m 2 /daily for 14 days as monotherapy, Kebudi et al [7] reported a 15% response rate (RR) in relapsed pediatric patients. Sandri et al [8] reported a successful use of Oral Etoposide at 50 mg/m 2 in children with recurrent ependymomas, showing a 40% RR. Oral Etoposide is well tolerated, with only mild adverse drug reactions like nausea, leucopenia, and alopecia.…”
Section: Introductionmentioning
confidence: 99%
“…There was a 2-week gap between cycles. Drug dosing and treatment schedule are based on previously published treatments for children with high-risk neuroblastoma [32], sarcomas and brain tumors [22,30,31,[33][34][35]. No further dose escalation has been planned for this group of patients.…”
Section: Study Design and Therapy Administrationmentioning
confidence: 99%
“…However, Brandes et al found that platinum-based regimes had no effect on overall survival, despite a partial or complete response in 31% [42]. Oral etoposide has also been reported as being able to maintain stable disease for a median of 7 months in a small group of patients with recurrent disease [43].…”
Section: Chemotherapymentioning
confidence: 97%